2020
DOI: 10.1038/s41598-020-61609-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of non-vitamin K-antagonist oral anticoagulants for retinal vascular diseases in patients with atrial fibrillation: Korean cohort study

Abstract: We investigated the prevalence of retinal vascular occlusion and intraocular bleeding and compare their risks in patients undergoing anticoagulant therapy, either with non-vitamin K-antagonist oral anticoagulants (NOAC) or warfarin. We performed a cohort study (January 2015 to April 2018) in 281,970 patients with nonvalvular atrial fibrillation (AF) using health claims in the nationwide database of the Health Insurance Review and Assessment service of Korea. A Cox-proportional hazard regression was used to cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
1
1
Order By: Relevance
“…However, these do not appear to be discussed in this study . Park et al found a higher hazard ratio for RVO but not for RAO with direct-acting oral anticoagulants. Diuretics will increase the plasma osmolality and induce prothrombotic status subsequently, and oral contraceptives are a well known factor of increasing the incidence of venous thromboembolism.…”
contrasting
confidence: 65%
“…However, these do not appear to be discussed in this study . Park et al found a higher hazard ratio for RVO but not for RAO with direct-acting oral anticoagulants. Diuretics will increase the plasma osmolality and induce prothrombotic status subsequently, and oral contraceptives are a well known factor of increasing the incidence of venous thromboembolism.…”
contrasting
confidence: 65%
“…They concluded that only edoxaban was associated with a significantly diminished risk of intraocular bleeding compared with warfarin. Moreover, a prospective cohort study conducted by Campello et al ( 15 ), enrolling 275 cases and 322 controls, found that there was a slightly increased incidence of bleeding in thrombophilia patients treated with NOACs. Subsequently, a large observational cohort study by Park et al ( 16 ) enrolled 27,496 patients with warfarin and 93,691 NOAC users and concluded that the risk of intraocular bleeding was lower in the NOAC group.…”
Section: Introductionmentioning
confidence: 99%